Development of Calculus Teaching Materials through Problem-Based Learning Model and Scientific Approach - Sufri Sufri; Feri Tiona Pasaribu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research is based on the relatively low literacy or problem solving ability and creative thinking level of students towards the teaching material for the "Calculus" course. In the mathematics education study program, calculus courses are prerequisites for many courses, including advanced calculus, real analysis, mathematical statistics, numerical methods, differential equations, initial values and boundary conditions, and complex number algebra. The purpose of this study is to improve the quality of learning seen from the aspect of the level of problem solving abilities, and students' creative thinking abilities, and to produce teaching materials for Calculus courses in the form of modules that meet the eligibility criteria, namely valid, practical and effective. From the aspect of the learning process the variables observed as indicators or benchmarks of research success are problem solving abilities, and students' creative thinking skills, while from the aspect of learning media the indicators of research success are the validity, practicality and effectiveness of the learning media used. The average value of the problem-solving ability of classically meticulous subjects in solving problems of Calculus learning material reaches 77.2 with a minimum completeness score of 80% (≥75%).